Impact of Pneumococcal Conjugate Vaccination of Infants on Pneumonia and Influenza Hospitalization and Mortality in All Age Groups in the United States - Lone Simonsen (American Society for Microbiology, 2011)
ABSTRACT A seven-valent pneumococcal conjugate vaccine (PCV7) introduced in the United States in 2000 has been shown to reduce invasive pneumococcal disease (IPD) in both vaccinated children and adults through induction of herd immunity. We assessed the impact of infant immunization on pneumococcal pneumonia hospitalizations and mortality in all age groups using Health Care Utilization Project State Inpatient Databases (SID) for 1996 to 2006 from 10 states; SID contain 100% samples of ICD9-coded hospitalization data for the selected states. Compared to a 1996–1997 through 1998–1999 baseline, by the 2005–2006 season, both IPD and pneumococcal pneumonia hospitalizations and deaths had decreased substantially in all age groups, including a 47% (95% confidence interval [CI], 38 to 54%) reduction in nonbacteremic pneumococcal pneumonia (ICD9 code 481 with no codes indicating IPD) in infants <2 years old and a 54% reduction (CI, 53 to 56%) in adults ≥65 years of age. A model developed to calculate the total burden of pneumococcal pneumonia prevented by infant PCV7 vaccination in the United States from 2000 to 2006 estimated a reduction of 788,838 (CI, 695,406 to 875,476) hospitalizations for pneumococcal pneumonia. Ninety percent of the reduction in model-attributed pneumococcal pneumonia hospitalizations occurred through herd immunity among adults 18 years old and older; similar proportions were found in pneumococcal disease mortality prevented by the vaccine. In the first seasons after PCV introduction, when there were substantial state differences in coverage among <5-year-olds, states with greater coverage had significantly fewer influenza-associated pneumonia hospitalizations among children, suggesting that PCV7 use also reduces influenza-attributable pneumonia hospitalizations. IMPORTANCE Pneumonia is the world’s leading cause of death in children and the leading infectious cause of death among U.S. adults 65 years old and older. Pneumococcal conjugate vaccination of infants has previously been shown to reduce invasive pneumococcal disease (IPD) among seniors through prevention of pneumococcal transmission from infants to adults (herd immunity). Our analysis documents a significant vaccine-associated reduction not only in IPD but also in pneumococcal pneumonia hospitalizations and inpatient mortality rates among both vaccinated children and unvaccinated adults. We estimate that fully 90% of the reduction in the pneumonia hospitalization burden occurred among adults. Moreover, states that more rapidly introduced their infant pneumococcal immunization programs had greater reductions in influenza-associated pneumonia hospitalization of children, presumably because the vaccine acts to prevent the pneumococcal pneumonia that frequently follows influenza virus infection. Our results indicate that seven-valent pneumococcal conjugate vaccine use has yielded far greater benefits through herd immunity than have previously been recognized.